ORGANIZATIONAL DETERMINANTS OF HEALTH INFORMATION UTILIZATION IN MAKING DECISION AMONG HEALTHCARE MANAGERS IN MOMBASA COUNTY, KENYA - Otieno, Moses Ochieng; Kawila (PhD), Dr. Caroline; Muiruri, Ms. Lillian (Journal of Health, Medicine and Nursing, 2020)
Purpose: This was a study based on Health Information Systems pillar. The objective was to examine organizational factors which influence health information utilization in making decision among healthcare managers in Mombasa County. Methodology: This was a Descriptive Survey Study design where desired data was obtained from selected respondents by semi-structured questionnaires. The research targeted a total of 303 healthcare managers in Mombasa County which comprised of 21 County Health Management Team (CHMT) members, 56 Sub-county Health Management Team (SCHMT) members from the four sub-counties, 43 facility In-Charges from the 43 public health facilities and 183 Heads of Departments (HODs). A sample size of 91 healthcare managers (30% of the target population) was used in the study with a response rate of 98.9% being achieved. Data was analyzed with SPSS version 23. Findings: Results revealed that organizational factors (Î²2 = 0.233; t = 4.552; p < 0.01) were significant predictors of health information utilization in making decision among healthcare managers in Mombasa County. These results imply that improvement in these variables (Feedback mechanisms, Supportive supervision and Resource availability on Health Information Systems) will enhance health information utilization in making decision. Unique contribution to theory, practice and policy: Implementation of the study findings will ensure that healthcare organizations have systems and infrastructure for improving interpersonal relationship among healthcare workers and managers, providing clear guidelines and defining roles and responsibilities related to HIS thus improving evidence-based decision making. When this is done, the study will have validated the theory of Evidence Based Health Information System by Carbone, (2009), on which the study was anchored. This theory further explains that there is need for a "catalyst" which is responsible for ensuring that the overall clinical care task is performed. Organizational factors are some of the catalysts referred to in the theory that when looked into will ensure an improved health outcome. The study recommends that the Ministry of Health (MOH) introduces Health Management Information Systems (HMIS) as a subject in the pre-service curriculum of all healthcare cadres in order to improve Health Information Systems (HIS) and facilitate proper prioritization of health needs, interventions and proper resource allocation.